Pengaruh Dimensi Motivasi Belajar terhadap Hasil Akademik dalam Mata Kuliah Statistika Dasar - Somawati, Somawati (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to investigate the extent to which learning motivation affects academic achievement in basic statistics courses. This research employs a quantitative approach with an explanatory correlational design. This design is used to test the effect of the independent variable, namely learning motivation, on the dependent variable, which is the academic results of students in basic statistics courses. The research population consists of third-semester students from the Computer Engineering Study Program at Indraprasta PGRI University, and 65 respondents were purposively selected from three existing classes. The instrument used was a Likert-scale questionnaire and final course grade data. Data processing resulted in a coefficient of determination R Square of 0.150 with a significance value of 0.021 (p < 0.05). The findings indicate that learning motivation contributes about 15 percent to students' academic results. In other words, motivation is proven to be important, but it is not the sole determining factor. The implications of this research encourage educators to design strategies that can enhance student motivation, especially in quantitative and analytical learning.